Sistem Pakar Identifikasi Penyakit Kulit Anjing Menggunakan Metode Certainty Factor - Hakim, Arnaz Malikul; Jusak, Jusak; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Dogs are common animal that found as pets in Indonesia. Indonesia as a tropical country has a high humidity, where fungi and parasites easily to multiply on animal skin. The fungi and parasites are one of the causes of dog skin diseases. Worsely, dog skin diseases can be transmitted to other animals as well as humans. When dog skin diseases are not treated properly they can excruciate the dog condition, because it can lead to the emergence of other diseases simultaneously, and it can even bring the dog to death.The limitation informative tools in identifying dog skin diseases can cause retardationin handling the disease. In this work, we provide an expert system to identify the dog skin diseases and give suggestion as to how to handle it. The skin diseases in dogs have similar symptoms between each other. The degree of belief of the symptoms determines the disease identification.Hence, in order to accommodate the identification process, an expert system is built by using the certainty factor method.Based on the result,it is shown that the expert system is able to identify dog skin disease with 91.67% accuracy derived from the twelve tests. The tests were done by the appointed expert in this area.